ANALISIS DAYA DUKUNG FONDASI TIANG PANCANG (STUDI KASUS PROYEK PEMBANGUNAN RUMAH SUSUN PEMERINTAHAN KABUPATEN INDRAGIRI HULU) - Nadhiratul Husni; Arif Sudaryanto; Lisa Trisnawati (Nusantara Hasana Berdikari, 2022)
Pile foundations are relatively long and slender rods that are used to transmit the foundation load through a layer of soil with low bearing capacity to a hard soil layer that has a high bearing capacity which is relatively deep compared to shallow foundations. The purpose of this study was to calculate the carrying capacity of a single pile, the efficiency of the pile group and the carrying capacity of the pile group from the sondir results. The calculation of the single pile bearing capacity is carried out using the Bagemann, deRuiter and Beringen methods. Pile group bearing capacity based on pile group efficiency using the Converse-Labarre Formula, Poulos and Davis, Los Angeles Group method. The results of the analysis of the calculation of the ultimate bearing capacity of the largest single pile foundation at a depth of 9 meters based on the Bageman Method (Qu) = 4,268.94 tons with (Qa) = 2,134.47 tons, and the smallest calculation analysis results at a depth of 9 meters based on the deRuiter and Beringen methods (Qu)= 1,154.99 tons with (Qa)= 577.49 tons. This is due to the effect of the maximum frictional resistance stated by deRuiter and Beringen which is 1.2 kg/cm2. The efficiency of the largest pile group in the P2 foundation variation with Eg = 0.947 and the smallest pile group efficiency on the P23 foundation variation with Eg = 0.062, this is because the pile efficiency depends on several factors including: the number, arrangement, and distance of the pile (Coduto, 1994) . The results of the analysis of the calculation of the bearing capacity of the largest pile group in the P23 foundation variation group with Qg = 38,685.13 tons and the smallest value in the P23 group variation with Qg = 823.50 tons, this is due to the efficiency of the pile group and the number of piles.